Coral-Associated Viral Assemblages From the Central Red Sea Align With Host Species and Contribute to Holobiont Genetic Diversity - Cárdenas, Anny; Ye, Jin; Ziegler, Maren; Payet, Jérôme P.; McMinds, Ryan; Vega Thurber, Rebecca; Voolstra, Christian R. (Frontiers in Microbiology, 2020)
Coral reefs are highly diverse marine ecosystems increasingly threatened on a global scale. The foundation species of reef ecosystems are stony corals that depend on their symbiotic microalgae and bacteria for aspects of their metabolism, immunity, and environmental adaptation. Conversely, the function of viruses in coral biology is less well understood, and we are missing an understanding of the diversity and function of coral viruses, particularly in understudied regions such as the Red Sea. Here we characterized coral-associated viruses using a large metagenomic and metatransciptomic survey across 101 cnidarian samples from the central Red Sea. While DNA and RNA viral composition was different across coral hosts, other biological traits such as coral life history strategies correlated with patterns of viral community composition. Coral holobionts were broadly associated with Mimiviridae and Phycodnaviridae that presumably infect fungal associates, Myoviridae and Siphoviridae that presumably target members of the bacterial phyla Actinobacteria, Firmicutes, and Proteobacteria, and Hepadnaviridae and Retroviridae that might affect the coral host. Genes involved in bacterial virulence and auxiliary metabolic genes were common in viral sequences, corroborating a contribution of viruses to the holobiont’s genetic diversity. Our work provides a first insight into Red Sea coral DNA and RNA viral assemblages and reveals that viral diversity is consistent with global coral virome patterns.